Vertical profiles and regional transport of ozone and aerosols in the Yangtze River Delta during the 2016 G20 summit based on multiple lidars. (15th August 2021) - Wang, Xinqi; Xiang, Yan; Liu, Wentao; Lv, Lihui; Dong, Yunsheng; Fan, Guangqiang; Ou, Jinping; Zhang, Tianshu
Abstract: The G20 summit of 2016 was held from September 4–5, and a series of stringent emission reduction measures were taken in Hangzhou, an economically developed city in the Yangtze River Delta (YRD), and its surrounding regions. This study analyzed the vertical and regional pollutant distributions and their interactions in Hangzhou during the summit. The results show that the concentration of PM2.5 decreased and the concentration of ozone increased. The average hourly PM2.5 concentration decreased by 43.67% during the control period compared with afterward, and PM2.5 transport was mainly from southern part of Anhui and southeastern part of Zhejiang. There were four occurrences of heavy ozone pollution during the observation period, and the maximum value reached 130.56 ppb. Vertical and horizontal transport mainly occurred at a height of 1–2 km. The Weather Research and Forecasting (WRF-Chem) model demonstrated that the most severe ozone pollution was affected by the northeast wind, and the downdraft created a continuous high concentration of ozone pollution. The correlation between the ozone concentration and the aerosol extinction coefficient was negative below 0.84 km and positive around 0.84–2 km. Highlights: Cooperative observation of mobile vehicle-based lidar and differential absorption lidar. Vertical and regional distribution of PM2.5 and ozone were analyzed during G20. Concentrations of PM2.5 declined, whereas concentrations of O3 increased. Accumulation of O3 under favorable meteorological conditions.